Prevalence and levels of IgG and IgM antibodies against Plasmodium falciparum and P. vivax in blood donors from Rondônia, Brazilian Amazon - Marcelo Urbano Ferreira; Luis Marcelo Aranha Camargo; Maria Esther de Carvalho; Regina Tomoko Ninomia; Luis Antonio Vieira Garcia; Francisco Roberto dos Santos (Memorias do Instituto Oswaldo Cruz, 1993)
Antibodies of IgG and IgM isotopes reacting with Plasmodium falciparum and P. vivax thick-smear antigens were searched for by the indirect fluorescent antibody test (IFAT) in a random sample of 230 blood donors at the transfusion centre of Porto Velho (HEMERON), Rondônia State, western Brazilian Amazon. A high prevalence of IgG seropositivity (32% against P. falciparum, 24% against P. vivax and 37% against either P. falciparum or P. vivax antigens) was detected among them, despite the fact that candidates reporting recent (<12 months) malaria attacks were not elegible. Only a small proportion of them had also detectable IgM antibodies to these antigens. These data suggest an intense, relatively recent exposure to malaria in such an urban population sample. However, parasitaemia (as detected by microscopical examination of Giemsa-stained thick smears) was patent in only one prospective donor. The antibody profile of blood donors was compared with that of healthy subjects of all age groups, living in a close endemic area (Candeias village, 21 km east of Porto Velho). The villagers were classified into two groups according to their history of a recent (<12 months) or a remote (>12 months) past malaria attack due to either P. falciparum or P. vivax. Extensive overlapping was observed when the distribution of antibody titres of healthy subjects from Candeias village with a recent and remote malaria history was compared. In conclusion, subjects with a recent or a remote malaria history could not be distinguished by sorological criteria alone.